The impact of new drug launches on the loss of labor from disease and injury: evidence from German panel data - Thi Mai Van Bui; Michael Stolpe (Kiel Institute for the World Economy (IfW), 2007)
This paper studies the evolution of early retirement due to disease and injury in the German labor force between 1988 and 2004. Using data from the German Federation of Public Pension Providers, the IMS Health Drug Launches database and the WHO Mortality Database, we show that new drug launches have substantially helped to reduce the loss of labor at the disease-level over time. We employ a variety of econometric methods to exploit the pseudo-panel structure of our dataset and find that in Western Germany alone each new chemical entity has on average saved around 200 working years in every year of the observation period. Controlling for individual determinants of health-related retirement, such as worker's age, sex and type of work, we also find evidence that the 2001 reform of pension laws has led to further reductions in the loss of labor from disease and injury.
Keywords: I18; J26; I12; 330; Early retirement; Rehabilitation services; Pension reform; Pseudo-panel data; Medical technology; Flexible Altersgrenze; Erwerbsunfähigkeit; Pharmazeutisches Produkt; Technischer Fortschritt; Ältere Arbeitskräfte; Arbeitsangebot; Rentenreform; Gesundheit; Schätzung; Deutschland